2021
DOI: 10.3389/fspor.2021.685117
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Health and Physical Activity in People With Major Depression in the Context of COVID-19

Abstract: Introduction: Major depression is a psychiatric disease associated with physical inactivity, which in turn affects mental and physical health. A randomized controlled trial is being implemented to facilitate physical activity in people with major depression. In March 2020, Swiss state authorities temporarily legislated a lockdown to contain the Coronavirus disease-19 (COVID-19), which influenced health, behavior and research. The aim of this study was to find out whether data gathered before and during/after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Finally, it could be that the Covid-19 pandemic may have affected the intervention. However, we were able to show that participants included before vs. after the outbreak of the pandemic did neither differ with regard to psychopathology nor physical activity behavior (Cody et al, 2021).…”
Section: Methodological Considerationsmentioning
confidence: 58%
“…Finally, it could be that the Covid-19 pandemic may have affected the intervention. However, we were able to show that participants included before vs. after the outbreak of the pandemic did neither differ with regard to psychopathology nor physical activity behavior (Cody et al, 2021).…”
Section: Methodological Considerationsmentioning
confidence: 58%
“…Finally, it could be that the Covid-19 pandemic may have affected the intervention. However, we were able to show that participants included before vs. after the outbreak of the pandemic did neither differ with regard to psychopathology nor physical activity behavior [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it also led to psychological problems such as stress, insomnia, denial, anger, and fear. 1,[4][5][6][7][8] Recent studies have indicated that adults diagnosed with COVID-19 may contribute to increased levels of depression and anxiety. [9][10][11][12] During the COVID-19 period, children in quarantine have experienced negative effects on their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Minimizing social interaction among parents, classmates, and friends was effective in controlling the pandemic. However, it also led to psychological problems such as stress, insomnia, denial, anger, and fear 1,4–8 . Recent studies have indicated that adults diagnosed with COVID‐19 may contribute to increased levels of depression and anxiety 9–12 .…”
Section: Introductionmentioning
confidence: 99%